Functional Role of Inflammasome Activation in a Subset of Obese Nonsmoking Patients with Severe Asthma - Ruggeri, Paolo; Caramori, Gaetano (American journal of respiratory and critical care medicine, 2019)
The authors examined induced sputum from 399 obese patients with asthma (66% females, mean [±SD] age, 48 ± 1 yr; body mass index [BMI], 33 ± 9; 89% under regular treatment with inhaled corticosteroids, 62% under regular treatment with a high dose [not otherwise specified] of inhaled corticosteroids, and 16% under regular treatment with systemic glucocorticoids; comorbidities [including bronchiectasis] and their treatment not reported) from the Severe Asthma Research Program-3 cohort and two control groups of 59 (61% females; mean age, 38 ± 1 yr) and 35 (51% females; mean age, 40 ± 1 yr) healthy overweight subjects with a mean (6 SD) BMI of 25 6 6 and 27 ± 5, respectively. The U-BIOPRED (Unbiased Biomarkers in Prediction of Respiratory Disease Outcomes) Consortia Project Team demonstrated inflammasome activation in induced sputum from patients (smoking and nonsmoking) with severe asthma compared with nonsmoking patients with mild/moderate asthma and healthy control subjects that was associated with sputum neutrophilia and increased IL-1ß protein levels (9). [...]obesity alone may influence NET formation (10) and NLRP3 inflammasome activation (11), and weight loss decreases peripheral blood neutrophil NET formation and inflammasome activation (12, 13). Furthermore, the authors provided no information about the diet of their subjects, and it has been demonstrated that in obese patients with stable asthma an acute challenge with a meal high in saturated fatty acids increases their sputum neutrophilia (13).